Working out and introduction of a uniform format of the accounting reporting (Путеводитель предпринимателя)
The Russian Federation has control over the activities of organizations conducted by thetax service, extra-budgetary funds, statistical offices, primarily on the basis of mandatory reporting to these bodies. Organizations interested in reducing to the minimum necessary paperwork and submit in a single service.